Delivering nuclear power: challenges for the Obama administration - Baker, Keith (2009)
This article considers two key problems that the Obama administration may face in respect of delivering a revival of nuclear power in the United States. It is shown that previous attempts to promote nuclear power have created an institutional infrastructure that exposes the U.S. government to considerable financial risk. if the Obama administration continues with its support for nuclear power, it risks billions of dollars of public money. It is also shown that the Obama administration's decisions regarding the management of nuclear waste have actually undermined the viability of nuclear power. It is concluded that the challenges are such that the U.S. federal government may have to assume direct control of any future nuclear program. - Reproduced.
Keywords: Nuclear weapons